Langerhans cell histiocytosis: Case series and literature review - Cardeña-Mamani, Rakel (2021)
Background: Langerhans cells histiocytosis is reported in approximately three out of every million children. It is of unknown origin, considered a clonal neoplasm, with a BRAF, RAS mutation, in the myeloid differentiation; depending on its presentation, both prognosis and survival are variable. Cases report: Three cases of patients aged 10, 11 and 9 years, diagnosed with Langerhans cell histiocytosis at an early age and followed-up are presented. Two of them had cranial tumors, and the remaining one with lesions in the femur and humerus, which progressed from unifocal unisystemic disease to multifocal, multisystemic disease. Conclusion: Langerhans cells histiocytosis should be considered in the differential diagnoses of rapidly progressing cranial tumors and bone tumors in childhood, due to its high frequency of bone involvement. The follow-up was performed by oncology, and management with the classification of multisystemic involvement.